Clinical Use of Next-Generation Sequencing in the Diagnosis of Wilson's Disease. (24th December 2015) - Németh, Dániel; Árvai, Kristóf; Horváth, Péter; Kósa, János Pál; Tobiás, Bálint; Balla, Bernadett; Folhoffer, Anikó; Krolopp, Anna; Lakatos, Péter András; Szalay, Ferenc
Abstract : Objective . Wilson's disease is a disorder of copper metabolism which is fatal without treatment. The great number of disease-causing ATP7B gene mutations and the variable clinical presentation of WD may cause a real diagnostic challenge. The emergence of next-generation sequencing provides a time-saving, cost-effective method for full sequencing of the whole ATP7B gene compared to the traditional Sanger sequencing. This is the first report on the clinical use of NGS to examine ATP7B gene. Materials and Methods . We used Ion Torrent Personal Genome Machine in four heterozygous patients for the identification of the other mutations and also in two patients with no known mutation. One patient with acute on chronic liver failure was a candidate for acute liver transplantation. The results were validated by Sanger sequencing. Results . In each case, the diagnosis of Wilson's disease was confirmed by identifying the mutations in both alleles within 48 hours. One novel mutation (p.Ala1270Ile) was found beyond the eight other known ones. The rapid detection of the mutations made possible the prompt diagnosis of WD in a patient with acute liver failure. Conclusions . According to our results we found next-generation sequencing a very useful, reliable, time-saving, and cost-effective method for diagnosing Wilson's disease in selected cases.